I am a monument : on Learning from Las Vegas - Vinegar, Aron (MIT Press, 2008)
"Learning from Las Vegas, originally published by the MIT Press in 1972, was one of the most influential and controversial architectural books of its era. Thirty-five years later, it remains a perennial bestseller and a definitive theoretical text. Its authors - architects Robert Venturi, Denise Scott Brown, and Steven Izenour - famously used the Las Vegas Strip to argue the virtues of the "ordinary and ugly" above the "heroic and original" qualities of architectural modernism. Learning from Las Vegas not only moved architecture to the center of cultural debates, it changed our ideas about what architecture was and could be." "In this provocative rereading of an iconic text, Aron Vinegar argues that Learning from Las Vegas is not only of historical interest but of absolute relevance to current critical debates in architectural and visual culture. Vinegar argues that to read Learning from Las Vegas only as an exemplary postmodernist text - to understand it, for example, as a call for pastiche or as ironic provocation - is to underestimate its deeper critical and ethical meaning, and to miss the underlying dialectic between skepticism and the ordinary, expression and the deadpan, that runs through the text."--Jacket